PENERAPAN MODEL PEMBELAJARAN SNOWBALL THROWING UNTUK MENINGKATKAN HASIL BELAJAR IPS KELAS V SDN 010 TANDUN - Kusyati, Kusyati; Zulkifli, Zulkifli; Kurniaman, Otang (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract : Problem in this study is the low value of the lesson IPS. This is because student are rarely given the opportunity to present theirs views, often play in learning, difficulty mastering the material. Based on these problems it is necessary to find a way to solve it by using appropiate learning model. Throwing snowball learning model provides an opportunity for student to be more achive in the learning and knowledge exchange to improve the learning outcomes of student in grade 5 IPS SDN 010 Tandun. Subejct in this study were students in grade 5 SDN 010 Tandun school year 2011/2012 with 29 student. This research is done in two cycles, cycle I held two meetings with one end and repeat the cycle 2 was also conducted 2 meetings and 1 time the daily test. Data collection instrument in this study is the observation sheets students. Teacher observation sheets and final replay test cycle. This research in the form of classroom action reseacrh. This study aims to improve learning outcomes in grade 5 IPS SDN 010 Tandun material, “Stroggle for independence”. The results of this study indicate that the learning model snowball throwing IPS can improve student learning outcomes. Classical completeness 62,06% students in cycle one and cycle two increased to 82,75%. This means, that the model can improve the learning snowball throwing in grade 5 SDN 010 Tandun. Keywords: Snowball throwing learning model, IPS learning outcome